E-Tendering readiness in construction: the posterior model. Issue 2 (3rd April 2018) - Al Yahya, Moath; Skitmore, Martin; Bridge, Adrian; Nepal, Madhav; Cattell, David
Abstract : Purpose: The purpose of this paper is to varied a conceptual model for e-Tendering readiness in any construction organisation prior of implementing e-Tendering system. Design/methodology/approach: Based on conceptual model called e-Tendering readiness model (e-TRM), this paper empirically examines the e-TRM's interactions and causal relationships between e-Tendering constructs and e-Tendering readiness. The paper uses the structural equation modelling technique to test the hypothesised positive inter-relationships. A questionnaire survey is conducted for respondents of construction organisations in Saudi Arabia to understand their current e-Tendering readiness and importance of e-Tendering variables. Findings: Supported by empirical evidence, this paper recognised that three out of nine constructs have direct influences on the e-Tendering readiness. However, one of the constructs, which is for the first time hypothesised and tested has the most effect. Research limitations/implications: Ultimately, the empirical test for the e-TRM is conducted in certain case (Saudi Arabia); however, the e-TRM needs to be tested in other case area for more verification. Practical implications: The study findings update previous information technology/information system models in construction by adding this tested model to the research literature on traditional and electronic tendering and the body of knowledge in the construction industry. Originality/value: The service providers construct is proposed and tested for the first time, which is necessary to support the successful e-Tendering implementation.